Improving energy‐efficient communications with a battery lifetime‐aware mechanism in IEEE802.16e wireless networks. (27th June 2012) - Chou, Li‐Der; Li, David Chunhu; Hong, Wei‐Yong; Fedak, Gilles; Li, Keqiu; Lin, Kai
SUMMARY Green network communication has recently received attention because of its economic and environmentally friendly benefits. Energy consumption significantly affects mobile subscriber stations in wireless broadband access networks. Efficient energy saving is an important and challenging issue because all mobile stations are powered by limited battery lifetimes. The IEEE 802.16e standard adopts the sleep mode operation for energy saving with three important parameters: idle threshold, initial sleep window and final sleep window. Adaptively adjusting these parameters to improve energy‐efficient communication is an open research topic. This paper proposes a battery lifetime‐aware energy‐saving mechanism to adaptively adjust three sleep mode parameters for mobile stations and extend batteries lives. The new mechanism considers effect factors, including residual battery lifetime and traffic load on mobile stations. Analytical sleep mode operation models were explored in this work. Our proposed mechanism was examined with a computer simulation using QualNet. The simulation results demonstrate that the proposed mechanism outperforms the IEEE 802.16e standard in the average lives of mobile stations, improving them by up to 30.08% with little increase in the average waiting delay. Copyright © 2012 John Wiley & Sons, Ltd.